Carry-over effect in forage rotations on newly reclaimed sandy soil in Egypt - Abdelhalim, Z.; Niemeläinen, Oiva; Hanna, I.A.; Rammah, A.M. (Fundacão de Estudos Agrários Luiz de Queiroz, 2001)
This study was carried out to investigate the carry-over effect of a preceding crop on the productivity of the following crop in various rotations in newly reclaimed lands in Egypt. The productivity of peanut (Arachis hypogaea L.), soyabean (Glycine max (L.) Merr.), maize (Zea mays L.) and pearl millet (Pennisetum glaucum (L.) R. Br.) in summer season were much higher following berseem (Trifolium alexandrinum L.) or lentil (Lens culinaris Medic) than after wheat (Triticum aestivum L.) or barley (Hordeum vulgare L.) in both years of the study. Soyabean was the best summer season pre-crop for lentil and berseem, whereas peanut was best for barley. Maize was a suprisingly good pre-crop in this study. The carry-over effect from pearl millet was inferior to that of maize. Of the winter season crops berseem had the most positive effect on the four summer crops studied. Winter season crops had a decreasing positive effect in the order: berseem, lentil, barley and wheat. The data suggest that, cropping systems on newly reclaimed sandy soils should include legume crops (soyabean or peanut in summer, and berseem or lentil in winter) to maximise production of the following crop.
Keywords: Ka; Egypti; rehuntuotanto; viljelykierto; ohra; apilat; maissi; soijapapu; maapähkinä; vehnä; barley; berseem; corn; lentil; pearl millet; peanut; soyabean; wheat